The Influence of Play Therapy on Levels of Anxiety to The School Children Age Who Have Hospitalization at Jempiring Room in Sanglah Hospital Denpasar - Savitri, Ni Putu Wiwik (Coping: Community of Publishing in Nursing, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Hospitalization is putting someone in the hospital for treatment. While undergoing the treatment process, children can have fear experience and anxiety. It can influence the child relationship with surrounding environment so that it can slow down healing process of children. One of the efforts can be to reduce the anxiety of children is to provide play therapy. This research aim to analyze the influence of play therapy on levels of anxiety to the school children age who have hospitalization. Based on introduction study at Jempiring Room in Sanglah Hospital Denpasar, the school children age who have treatment showed response of anxiety such as crying, asked home, and shouting. The research design were pre experiment with one group pre-post test design. The population of the research were 32 children and the sample is 30 children. Method of sampling in this research were non probability sampling with consecutive sampling. Data collecting method was done interview and observation using a questionnaire HRS-A levels of anxiety. The data was collected before and after play therapy. The results pre play therapy measurement showed that not experiencing anxiety (0%), mild anxiety (20%), moderate anxiety (56,3%), severe anxiety (26,7%), and heavy anxiety (0%). Meanwhile post play therapy measurement showed that not experiencing anxiety (26,7%), mild anxiety (20%), moderate anxiety (26,7%), severe anxiety (0%), and heavy (0%). Wilcoxon test showed a significant value 0,000 < 0,05, so Ho is rejected, it is mean there is influence of play therapy on levels of anxiety to the school children age who have hospitalization. Based on the result, it is suggested for pediatric nurses to implement play therapy to reduce the anxiety on children during treatment. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Hospitalization of children; Levels of anxiety; Play therapy